Digital transformation of the banking system and its influence on macroeconomic dynamics - Fiapshev, A.B.; Afanasyeva, O.N. (Opción, 2019)
The aim of the study is to investigate digital transformation of the Russian banking system and possibility of its influence on macroeconomic dynamics via methods of poll of representatives of bank community regarding their vision of the most important factors of development of the Russian banking system. As a result, the greatest total share of influence is occupied by group of factors of mesolevel, namely factors of subgroup situation in the bank sphere. In conclusion, the technology factor operating in the direction of large-scale digitalization of bank activity has the expressed restrictions in expansion of credit investments in economic development.